System advisor model (SAM) simulation modelling of a concentrating solar thermal power plant with comparison to actual performance data - Emeka K. Ezeanya; Gholam H. Massiha; William E. Simon; Jonathan R. Raush; Terrence L. Chambers (Cogent Engineering, 2018)
This paper is focused on the modelling and simulation of a 50 kW concentrated solar power (CSP) plant located in Crowley, Louisiana. The model was developed using system advisor model (SAM). The objective is to develop a predictive model (using SAM) to characterize the performance of the power plant and, thus, aid the analysis and evaluation of the plant’s performance. The power plant is a research facility of the Solar Thermal Applied Research and Testing (START) Lab. The model was validated by comparing its predictions with the actual plant data. The comparison showed a good correlation between the predicted results and the actual plant data. The validated model was then used to perform parametric analyses across different locations. The analyses showed that by operating the power plant at the optimal combination of solar multiple and hours of storage, we can achieve about 70% reduction in the cost of electrical energy.